Innovative funding solution for special projects: Crowd funding - Sentot Imam Wahjono; Anna Marina; Muhammad Fikry; Anggraeni . (Journal of Economics, Business, and Accountancy Ventura, 2015)
The aim of this paper is to examine the influence of crowd funding knowledge, applica-tion, platform, and project initiator toward successful crowd funding. This study conducted by quantitative approach, data have been collected with web-based ques-tionnaires via Kickstarter.com direct message and e-mail to 200 successful crowd funding project initiators as a sample and as much 152 sets questionnaire returned by a complete answer and should be analyzed further. Deployment and data collection take 3 month from October to December 2013. This study found evidence that crowd funding knowledge, crowd funding application, crowd funding platform, and project initiator has positive and significant relationship toward the success of crowd funding. The implication from this research is crowd funding can be a source of capital to finance the projects, not just rely on traditional sources of financing just like banking and capital markets. Crowd funding can be innovative funding solution.